Simulation Model of Production System Using Dynamic System Approach to Increase Production Capacity Tofu Factory - Tita Talitha; Rexza Berliyana (OPSI, 2022)
The speed in distributing the products of the industry is influenced by the speed of production produced by the industry itself. SMEs know that ECO is one of the manufacturing industries engaged in food manufacturing. there are obstacles (problems) that are experienced, namely the occurrence of inequality between the production capacity of tofu that can be produced and the demand for tofu that must be met. The purpose of this study is to increase the production capacity of Tofu Eco SMEs in terms of increasing working time. The method used in this research is the dynamic system method using the PLE vensim software. The results of the study show that based on the actual system conditions, it is known that there are 25 workers with 8 working hours per day, and an average production capacity of 957 barrels per month is obtained month with an average demand of 1005 barrels /month. The results of the alternative simulation I, have an average production capacity of 1,080 barrels/month. The results of the scenario II simulation show that the average production capacity is 1,230 barrels/month. From the simulation results of alternative scenarios, it can be seen that for production demand below 1,080 barrels/month, the alternative used is to add 1 hour (60 minutes) of overtime, while for requests above 1,079 barrels/month with a maximum production demand of 1,255 barrels/month, alternative scenarios can be used. II with the addition of 2 hours 30 minutes (150 minutes) of overtime.